The Possibility of the Application of Requirements Knowledge Management Systems in accordance with standard ISO 30401:2018/ A Case Study at Middle Technical University- Technical College of Management / Baghdad: Kemungkinan Penerapan Sistem Manajemen Persyaratan sesuai dengan standar ISO 30401:2018 / Studi Kasus di Universitas Teknik Menengah - Sekolah Tinggi Manajemen / Baghdad - Aljabi, Eslam Talib (Academia Open, 2026)
General Background: Knowledge management systems play a crucial role in supporting organizational learning and decision-making in modern institutions. Specific Background: ISO 30401:2018 provides a structured framework for implementing knowledge management systems across organizations. Knowledge Gap: Limited empirical evaluation exists regarding how ISO-based knowledge management requirements are applied and their contribution to organizational performance. Aims: This study evaluates the application of knowledge management system requirements based on ISO 30401 and examines their role in improving institutional practices. Results: The findings indicate that structured knowledge processes, including creation, sharing, and application, are associated with improved coordination, decision-making, and administrative performance, although implementation levels vary across organizations. Novelty: The study applies an ISO-based framework to systematically assess knowledge management practices within organizational contexts. Implications: The results highlight the importance of institutional commitment and continuous learning in implementing knowledge management systems aligned with international standards. Keywords: Knowledge Management, ISO 30401, Organizational Performance, Knowledge Systems, Institutional Development Key Findings Highlights Structured knowledge processes support internal coordination and efficiency Variation observed in organizational readiness and system implementation Standard-based frameworks guide systematic knowledge practices